Structurally enhanced ferroelectric articles and methods of making and using same - Patents.com

JP2025506167AActive Publication Date: 2025-03-07WL GORE & ASSOC INC +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024547505
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-11
Filing Date
2023-02-06
Publication Date
2025-03-07
Estimated Expiration
2043-02-06

Smart Images

  • Figure 2025506167000001_ABST
    Figure 2025506167000001_ABST
Patent Text Reader

Abstract

Various aspects of the present disclosure relate to devices, systems and methods including a ferroelectric article. The ferroelectric article can include a composite film having a first side and a second side, a first electrode electrically connected to the first side of the composite film, and a second electrode electrically connected to the second side of the composite film. The composite film can include a ferroelectric material and a polymeric reinforcement film.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of Provisional Application No. 63 / 309,338, filed February 11, 2022, which is incorporated herein by reference in its entirety for all purposes.

[0002] FIELD OF THEINVENTION The present disclosure relates generally to ferroelectric materials reinforced with structural components to create articles of manufacture that exhibit superior ferroelectric properties and improved structural properties. [Background technology]

[0003] 2. Background of the Invention Ferroelectricity is the property of certain materials to have a spontaneous electric polarization that can be reversed by the application of an external electric field. Ferroelectric materials also exhibit piezoelectric properties. There are a variety of ferroelectric materials, including ferroelectric ceramics and ferroelectric polymers. Some of these ferroelectric materials also exhibit relaxor ferroelectric properties. Examples of ferroelectric polymers include, but are not limited to, vinylidene fluoride (VDF) copolymers (e.g., poly(vinylidene fluoride-trifluoroethylene) (p(VDF-TrFE)) and VDF terpolymers (e.g., poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (p(VDF-TrFE-CFE) and poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) (p(VDF-TrFE-CTFE))).

[0004] Applications of ferroelectric materials include, but are not limited to, sensors, energy storage, non-volatile memory storage, transducers, actuators, and electrocaloric heating / cooling. However, many of these ferroelectric materials are insufficiently strong or formable for use in certain applications. Therefore, reinforcements are often included when manufacturing ferroelectric articles. Many reinforcements may adversely affect electrical performance (compared to unsupported ferroelectric materials) and / or suffer from lack of strength, lack of adequate stiffness / flexibility, or may not be sufficiently inert to the environmental conditions (chemical stability, thermal stability, etc.) of the target application. Finally, many reinforcements may not durably bond the ferroelectric material and / or electrodes, or may need to be removable.

[0005] The problem to be solved is to provide a ferroelectric article comprising a reinforced ferroelectric material, where the presence of the reinforcement provides desired mechanical properties and allows for the formation of thinner, stronger articles with electroactivity suitable for a variety of applications. Summary of the Invention

[0006] Summary of the Invention The above problems have been solved by providing a ferroelectric article comprising an electrode electrically bonded to a composite film in which a ferroelectric material is durably bonded to a polymer reinforcement membrane. The mechanical reinforcement allows for the formation of thin, strong and durable films with electrical activity suitable for a variety of product applications. Thinner films allow for higher polarization when stimulated with lower driving voltages and improve film handling to increase the ability to include additional processing steps (e.g., deposition of electrodes, formation of multilayers and composites with additional materials such as VDF terpolymer / relaxer ferroelectrics), simplifying fabrication into end-use articles / devices. The ferroelectric article can include multiple durable composite films arranged in various configurations (stacks, spirals, etc.).

[0007] According to one example ("Example 1"), a ferroelectric article includes a composite film having a first side and a second side, where the composite film includes a ferroelectric material and a polymeric reinforcement membrane, a first electrode electrically connected to the first side of the composite film, and a second electrode electrically connected to the second side of the composite film.

[0008] According to another example ("Example 2"), in addition to Example 1, the polymer-reinforced membrane comprises a densified and / or contracted membrane that includes macrostructured folds and / or microfolded fibrils.

[0009] According to another example ("Example 3"), in addition to Example 1, the ferroelectric material includes a ferroelectric polymer, a ferroelectric ceramic, or a combination thereof.

[0010] According to another example ("Example 4"), in addition to the previous examples, the ferroelectric polymer comprises a vinylidene difluoride (VDF) copolymer or terpolymer.

[0011] According to another example ("Example 5"), in addition to the previous examples, the ferroelectric polymer comprises one or more of poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (VDF-TrFE-CFE), poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) (P(VDF-TrFE-CTFE), poly(vinylidene fluoride-trifluoroethylene) (VDF-TrFE), or combinations thereof.

[0012] According to another example ("Example 6"), in addition to the above examples, the ferroelectric ceramic may be barium strontium titanate (BST), barium zirconium titanate (BZT), PZT (lead, zirconium, titanium, oxygen), PbTiO3 (PT), Pb(Mg 1 / 3 Nb 2 / 3 )O3(PMN), Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3(PMN-PT), LiTaO3 or combinations thereof.

[0013] According to another example ("Example 7"), in addition to the previous examples, the ferroelectric ceramic includes one or more of nanoparticles, nanowires, nanorods, nanocubes, nanofillers, or combinations thereof.

[0014] According to another example ("Example 8"), in addition to the previous examples, the ferroelectric material includes a ferroelectric polymer and a ferroelectric ceramic particle filler.

[0015] According to another example ("Example 9"), in addition to the previous examples, the polymer-reinforced membrane comprises a microporous membrane having pores, and the microporous membrane comprises a polyolefin, a fluorinated polyolefin, or a combination thereof.

[0016] According to another example ("Example 10"), in addition to the previous examples, the polymer reinforced membrane comprises one or more of ultra-high molecular weight polyethylene (UHMWPE), polytetrafluoroethylene (PTFE), polyparaxylylene (PPX), vinylidene fluoride (VDF) copolymer (VDF-co-TFE or TrFE), ethylenetetrafluoroethylene (ETFE), poly(tetramethyl-p-silphenylene siloxane) (PTMPS), or combinations thereof.

[0017] According to another example ("Example 11"), in addition to the previous examples, the polymer-reinforced membrane includes an expanded polymer having a microstructure of nodes interconnected by fibrils and a void volume defining a plurality of pores, an expanded polymer having a substantially only fibril microstructure and a void volume defining a plurality of pores, or a combination thereof.

[0018] According to another example ("Example 12"), in addition to Example 11, the expanded (expanded, expanded, stretched or foamed) polymer comprises one or more of expanded polytetrafluoroethylene (ePTFE), expanded ultra-high molecular weight polyethylene (ePE), expanded polyparaxylylene (ePPX), expanded VDF-co-TFE copolymer, expanded VDF-co-TrFE copolymer, expanded ethylenetetrafluoroethylene (eETFE), expanded poly(tetramethyl-p-silphenylenesiloxane (ePTMPS), or combinations thereof.

[0019] According to another example ("Example 13"), further to Examples 11 or 12, the expanded polymer node, fibril, or combination thereof microstructure is partially or completely coated with a conductive metal coating to define a coated microstructure, and further, the coated microstructure retains at least a portion of the void volume after coating.

[0020] According to another example ("Example 14"), in addition to the previous examples, the ferroelectric material forms a coating on the reinforcing film.

[0021] According to another example ("Example 15"), in addition to Examples 11 or 12, the ferroelectric material is partially or completely absorbed within a void volume of the reinforced film.

[0022] According to another example ("Example 16"), in addition to the previous examples, the ferroelectric polymer comprises one or more of poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (VDF-TrFE-CFE), poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) (P(VDF-TrFE-CTFE)), poly(vinylidene fluoride-trifluoroethylene) (VDF-TrFE), or combinations thereof, and further, the ferroelectric polymer is partially or completely absorbed within a reinforcing membrane of expanded ePTFE.

[0023] According to another example ("Example 17"), in addition to the previous examples, the composite film has a thickness of 1 μm or more and 20 μm or less.

[0024] According to another example ("Example 18"), in addition to Example 17, the composite film has a thickness of 1 μm or more and 10 μm or less.

[0025] According to another example ("Example 19"), in addition to the previous examples, the polymer-reinforced membrane has a mass per area of ​​5 g / m 2 The following is the result.

[0026] According to another example ("Example 20"), in addition to Example 19, the polymer-reinforced membrane has a mass per area of ​​4 g / m 2 The following is the result.

[0027] According to another example ("Example 21"), in addition to Example 19, the polymer-reinforced membrane has a mass per area of ​​3 g / m 2 The following is the result.

[0028] According to another example ("Example 22"), in addition to the above examples, the composite film has a total mass, and further includes a reinforcing film of 20 wt% or less based on the total mass of the composite film, and a ferroelectric material of 80 wt% or more based on the total mass of the composite film.

[0029] According to another example ("Example 23"), in addition to the above examples, the composite film has a total mass, and further includes a reinforcing membrane of 15 wt% or less based on the total mass of the composite film, and a ferroelectric material of 85 wt% or more based on the total mass of the composite film.

[0030] According to another example ("Example 24"), in addition to the previous examples, the composite film has a total mass, and further includes a reinforcing film of 10 wt% or less based on the total mass of the composite film, and a ferroelectric material of 90 wt% or more based on the total mass of the composite film.

[0031] According to another example ("Example 25"), in addition to the previous examples, the reinforced membrane is biaxially oriented, has a machine direction (MD) matrix tensile strength of at least 30 MPa, and a transverse direction (TD) matrix tensile strength of at least 30 MPa.

[0032] According to another example ("Example 26"), in addition to Example 19, the ratio of MD matrix tensile strength to TD matrix tensile strength is 1.0:0.1 to 0.1:1.0.

[0033] According to another example ("Example 27"), in addition to Examples 19-21, the reinforced film comprises a porosity of at least 30% as measured before adding the ferroelectric material.

[0034] According to another example ("Example 28"), in addition to the previous examples, the top electrode and / or the bottom electrode include a) a layer of conductive metal of alumina having a thickness of 80 nm or less, b) a layer of conductive thermoplastic of poly(3,4-ethylenedioxythiophene) polystyrenesulfonate (PEDOT:PSS), c) a layer of conductive ink including silver nanoparticles or silver nanowire ink deposited by digital printing, spraying, screen printing, or any combination of a, b, or c.

[0035] According to another example ("Example 29"), in addition to the previous examples, the ferroelectric composite includes multiple composite films in a stacked configuration.

[0036] According to another example ("Example 30"), in addition to the previous examples, the plurality of composite films includes a laminated structure.

[0037] According to another example ("Example 31"), in addition to Examples 28 or 30, at least one of the composite films in the stack configuration is different from at least one of the other composite films in the material.

[0038] According to another example ("Example 32"), in addition to Examples 28-31, at least one of the composite films in the stack configuration is of a different thickness than at least one of the other films in the material.

[0039] According to another example ("Example 33"), in addition to Examples 28-32, at least one of the composite films in the stack configuration has a different strength than at least one of the other films in the material.

[0040] According to another example ("Example 34"), in addition to Examples 27-31, at least one of the composite films in the stack configuration is oriented differently than at least one of the other films in the material.

[0041] According to another example ("Example 35"), a device includes the ferroelectric article of any of the previous examples.

[0042] According to another example ("Example 36"), a method for making a ferroelectric article includes providing a polymer reinforced membrane having a first side and a second side, wherein the polymer reinforced membrane has a microstructure of nodes interconnected by fibrils, or a microstructure of substantially only fibrils, the microstructure further defining a void volume that defines a plurality of pores, applying a ferroelectric material to the polymer reinforced membrane to form a reinforced ferroelectric composite, and applying at least one first electrode to the first side and at least one second electrode to the second side of the reinforced ferroelectric composite to form a ferroelectric article.

[0043] The foregoing examples are merely examples and should not be construed as limiting or narrowing the scope of any of the inventive concepts otherwise provided by this disclosure. While several examples have been disclosed, still other embodiments will become apparent to those skilled in the art from the following detailed description, which shows and describes illustrative examples. Accordingly, the drawings and detailed description are to be regarded as illustrative in nature and not restrictive. [Brief description of the drawings]

[0044] BRIEF DESCRIPTION OF THE DRAWINGS The accompanying drawings are included to provide a further understanding of the disclosure, and are incorporated in and constitute a part of this specification, illustrating embodiments and, together with the description, serve to explain the principles of the disclosure.

[0045] [Figure 1] FIG. 1 is a cross-sectional scanning electron micrograph (SEM) of the monolithic film of Example 1.

[0046] [Diagram 2] FIG. 2 is a graphical representation of differential scanning calorimetry (DSC) results for the samples prepared in Examples 1 and 2.

[0047] [Diagram 3] FIG. 3 is a graphical representation of the machine (downweb) direction tensile test results of the monolithic films prepared in Examples 1 and 2.

[0048] [Figure 4] FIG. 4 is a graphical representation of the transverse tensile test results of the monolithic films prepared in Examples 1 and 2.

[0049] [Diagram 5] FIG. 5 is a cross-sectional SEM of the annealed monolithic film of Example 2.

[0050] [Figure 6] FIG. 6 is a graphical representation of the voltage breakdown test shown in the Wavelet plot of the annealed monolithic film of Example 2.

[0051] [Figure 7] FIG. 7 is a graphical representation of the polarization data for the monolithic film of Example 2.

[0052] [Figure 8] FIG. 8 is a cross-sectional SEM of the composite film prepared in Example 3.

[0053] [Figure 9]FIG. 9 is a cross-sectional SEM of the composite film prepared in Example 4.

[0054] [Figure 10] FIG. 10 is a graphical representation of the polarization data for the composite film of Example 4.

[0055] [Figure 11] FIG. 11 is a cross-sectional SEM of the composite film prepared in Example 5.

[0056] [Figure 12] FIG. 12 is a graphical representation of the polarization data for the composite film of Example 6.

[0057] [Figure 13] FIG. 13 is a cross-sectional SEM of the composite film prepared in Example 7.

[0058] [Figure 14] FIG. 14 is a graphical representation of the polarization data for the composite film of Example 7.

[0059] [Figure 15] FIG. 15 is a graphical representation of the polarization data for the composite film of Example 8.

[0060] [Figure 16] FIG. 16 is a graphical representation of the polarization data for the composite film of Example 9.

[0061] [Figure 17] FIG. 17 is a graphical representation of the polarization data for the composite film of Example 10.

[0062] [Figure 18] FIG. 18 is a graphical representation of the polarization data for the composite film of Example 11.

[0063] [Figure 19] FIG. 19 is a cross-sectional SEM of the composite film prepared in Example 12.

[0064] [Figure 20] FIG. 20 is a graphical representation of the tensile test results in the machine direction (MD) and transverse direction (TD) of two different reinforced terpolymer-based composite films prepared in Examples 12 and 14.

[0065] [Figure 21] FIG. 21 is a graphical representation of the polarization data for the composite film of Example 12.

[0066] [Figure 22] FIG. 22 is a graphical representation of the polarization data for the composite film of Example 13.

[0067] [Figure 23] FIG. 23 is a graphical representation of dynamic tensile test results in the transverse direction (TD) of the composite film prepared in Example 14.

[0068] [Figure 24] FIG. 24 is a graphical representation of the polarization data for the composite film of Example 14.

[0069] [Diagram 25] FIG. 25 is a cross-sectional SEM of the composite film prepared in Example 15.

[0070] [Figure 26] FIG. 26 is a graphical representation of the polarization data for the composite film of Example 15.

[0071] [Figure 27] FIG. 27 is a graphical representation of the polarization data for the composite film of Example 16.

[0072] [Figure 28] FIG. 28 is a cross-sectional SEM of the composite film prepared in Example 18.

[0073] [Figure 29]FIG. 29 is a graphical representation of the polarization data for the composite film of Example 18. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0074] Detailed Description of the Invention Those skilled in the art will readily appreciate that the various aspects of the present disclosure may be implemented by any number of methods and devices configured to perform the intended functions. It should also be noted that the accompanying figures referenced herein are not necessarily drawn to scale and may be exaggerated to illustrate various aspects of the present disclosure, and in that regard, the figures should not be construed as limiting.

[0075] definition As used herein, "electroactive polymer" or "EAP" refers to a polymer that exhibits a change in size or shape when stimulated by an electric field.

[0076] As used herein, "piezoelectric" refers to a material that can store an electric charge in response to an applied mechanical stress. This is a reversible process in which a mechanical strain is produced internally due to the reversible piezoelectric effect, which is caused by an applied electric field.

[0077] As used herein, "ferroelectric material" refers to a material capable of spontaneous electric polarization that can be reversed or switched by an external electric field. Examples include ferroelectric ceramics, ferroelectric polymers, and combinations thereof. Typically, ferroelectrics are only observed below a certain phase transition temperature called the Curie temperature (TC), above which they become paraelectric, the spontaneous polarization disappears, and the ferroelectric material is converted to the paraelectric state.

[0078] As used herein, "ferroelectric polymer" refers to a group of crystalline polar polymers that are also ferroelectric, meaning that they maintain a permanent electric polarization that can be reversed or switched with an external electric field.

[0079] As used herein, "relaxor ferroelectrics" refers to a group of ferroelectric materials that exhibit high electrostriction: they change shape, i.e., their surface area increases and their thickness decreases, upon the application of an electric field.

[0080] As used herein, a "relaxor ferroelectric polymer" refers to a polymer that exhibits both a high dielectric constant and low remanent polarization, thus enabling much higher energy density and greater charge / discharge efficiency than conventional ferroelectrics in capacitive energy storage applications.

[0081] As used herein, a "ferroelectric article" refers to a composite film including a polymeric reinforcement film (non-removable) + a ferroelectric material, said composite film having a first side and a second side, at least one electrode electrically connected to the first side and at least one electrode connected to the second side.

[0082] As used herein, "electrocaloric effect" refers to the phenomenon whereby a material with a dipolar component, i.e., specific dielectric properties, exhibits a reversible change in temperature under an applied electric field under adiabatic conditions.

[0083] As used herein, the terms "densification", "shrinkage" or "structuring" are used interchangeably to refer to a polymer-reinforced membrane that has been densified in one or more of the transverse or machine directions prior to application of the ferroelectric material. It should be understood that densification is not limited to one direction. It can be performed in the transverse, machine or both directions, either sequentially or simultaneously. In one exemplary embodiment, the polymer-reinforced membrane is densified in the transverse direction prior to application of the ferroelectric polymer material. The polymer-reinforced membrane that undergoes densification forms macro-structured folds and / or micro-folded fibrils within the membrane, providing the polymer-reinforced membrane with low modulus and flexibility. The densified polymer-reinforced membrane can also exhibit out-of-plane features such as membrane wrinkles or folds, including, but not limited to, methods described in EP 3061598 A1 to Zaggl et al. and U.S. Pat. No. 9,849,629 to Zaggl et al. It should be noted that heat or solvent shrinking, or other suitable methods may alternatively be used to non-mechanically "densify" the polymer-reinforced membrane.

[0084] Polymer-reinforced membrane The polymer-reinforced membrane is a microporous membrane that can be prepared from a variety of polymers. In one embodiment, the polymer-reinforced membrane comprises a fibrillated microstructure. In a preferred embodiment, the fibrillated microstructure comprises nodes interconnected by fibrils (see U.S. Patent No. 3,953,566 to Gore for examples of node and fibril microstructures).

[0085] The polymer-reinforced membranes are prepared from fibrillizable polymers. Specific examples of fibrillizable polymers (e.g., capable of being processed into membranes having a microstructure of nodes and fibrils) include, but are not limited to, ultra-high molecular weight polyethylene (UHMWPE) (Sbriglia, U.S. Pat. No. 10,577,468), polylactic acid (PLLA, Sbriglia, U.S. Pat. No. 9,732,184), copolymers of vinylidene fluoride and tetrafluoroethylene or trifluoroethylene (e.g., VDF-co-(TFE or TrFE) poly(ethylene glycol). No. 10,266,670 to Marr and Sbriglia), poly(ethylene tetrafluoroethylene) (ETFE, Sbriglia U.S. Pat. No. 9,932,429), polyparaxylylene (PPX, Sbriglia U.S. Pat. App. Pub. No. 2016-0032069), polytetrafluoroethylene (PTFE, Gore U.S. Pat. No. 3,315,020; Gore U.S. Pat. No. 3,953,566; Baille U.S. Pat. No. 7,083,225), and (tetramethyl-p-silphenylene siloxane) (PTMPS) (see International Patent Application Publication No. WO 2021 / 202628 A1).

[0086] In at least one embodiment, the polymer-reinforced membrane is a porous fluoropolymer membrane. In at least one exemplary embodiment, the polymer-reinforced membrane is a polytetrafluoroethylene (PTFE) membrane or an expanded polytetrafluoroethylene (ePTFE) membrane. In a preferred embodiment, the polymer-reinforced membrane is an expanded polytetrafluoroethylene membrane. In this specification, the expanded polytetrafluoroethylene (ePTFE) membrane prepared according to the method described in U.S. Patent No. 7,306,729 to Bacino et al., U.S. Patent No. 3,953,566 to Gore, U.S. Patent No. 5,476,589 to Bacino, or U.S. Patent No. 5,183,545 to Branca et al. can be used here. In a preferred embodiment, the polymer-reinforced membrane is an ePTFE membrane as described in U.S. Patent No. 7,306,729.

[0087] It will be understood that for convenience throughout this application, the term "PTFE" is used herein and is intended to include not only polytetrafluoroethylene, but also expanded PTFE, expanded modified PTFE, and copolymers of expanded PTFE, such as those described in U.S. Pat. No. 5,708,044 to Branca, U.S. Pat. No. 6,541,589 to Baillie, U.S. Pat. No. 7,531,611 to Sabol et al., U.S. Pat. No. 8,637,144 to Ford, and U.S. Pat. No. 9,139,669 to Xu et al.

[0088] The porous fluoropolymer membrane can also comprise a polymeric material comprising a functionalized tetrafluoroethylene (TFE) copolymer material, where the functionalized TFE copolymer material comprises a functionalized copolymer of TFE and PSVE (perfluorosulfonyl vinyl ether), or TFE and other suitable functional monomers (such as, but not limited to, vinylidene fluoride (VDF), vinyl acetate, or vinyl alcohol). The functionalized TFE copolymer material can be prepared, for example, according to the method described in U.S. Pat. No. 9,139,707 to Xu et al. or U.S. Pat. No. 8,658,707 to Xu et al.

[0089] In one embodiment, the polymer-reinforced membrane has an areal density of 5 g / m 2 Below, 4g / m 2 Below 3g / m 2 Below, 2g / m 2 or less than 1g / m 2 In another embodiment, the polymer-reinforced membrane has an areal density in the range of 5 g / m 2 ~0.01g / m 2 , 4g / m 2 ~0.1g / m 2 , 3g / m 2 ~0.1g / m 2 , 2g / m 2 ~0.1g / m 2 , 4g / m 2 ~0.2g / m 2 or 3 g / m 2 ~0.2g / m 2 It is.

[0090] In another embodiment, the polymer-reinforced membrane is 1 cm or less in thickness, 0.5 cm or less, 0.1 cm or less, or 0.01 cm or less in thickness. In another embodiment, the polymer-reinforced membrane is at least 0.05 μm, at least 0.1 μm, or at least 0.2 μm in thickness. In another embodiment, the polymer reinforced membrane has a thickness ranging from 0.5 cm to 0.05 μm, 5 mm to 0.05 μm, 1 mm to 0.05 μm, 500 μm to 0.05 μm, 100 μm to 0.05 μm, 50 μm to 0.05 μm, 40 μm to 0.05 μm, 30 μm to 0.05 μm, 20 μm to 0.05 μm, 15 μm to 0.05 μm, 40 μm to 0.1 μm, 30 μm to 0.1 μm, 20 μm to 0.1 μm, 20 μm to 0.1 μm, 15 μm to 0.1 μm, 10 μm to 0.1 μm, 40 μm to 0.2 μm, 30 μm to 0.2 μm, 20 μm to 0.2 μm, or 10 μm to 0.2 μm.

[0091] The polymer-reinforced membrane (before coating or imbibing) has a porosity of at least 30%, at least 40%, at least 50%, at least 60%, at least 70% or at least 80%. In one embodiment, the polymer-reinforced membrane has a porosity in the range of 50%-98%, 50%-95%, 50%-90% or 50%-85%.

[0092] The polymer-reinforced membrane has a matrix tensile strength (MTS) in both the machine direction (MD) and the transverse direction (TD) (orthogonal to the MD) of at least about 30 MPa, at least about 50 MPa, at least about 100 MPa, at least about 150 MPa, at least about 200 MPa, or at least 300 MPa. With respect to matrix tensile strength, the polymer-reinforced membrane can be unbalanced (strength in one direction significantly different from strength in the orthogonal direction) or balanced (strengths in MD and TD are similar). In another embodiment, the polymer-reinforced membrane has a ratio of matrix tensile strengths determined as MD:TD of about 0.1:1.0 to 1.0:0.1, or about 0.5:1.0 to 1.0:0.5, or about 0.7:1.0 to 1.0:0.7.

[0093] In a preferred embodiment, the polymer-reinforced membrane is a structured (also referred to herein as "densified") membrane. Simply put, a densified polymer-reinforced membrane forms macro-structured folds and / or micro-folded fibrils within the membrane, providing the polymer-reinforced membrane with low modulus and flexibility. Densified polymer-reinforced membranes may also exhibit out-of-plane features such as wrinkles or folds ("buckles") within the membrane, including, but not limited to, methods described in EP 3061598 A1 to Zaggl et al. and U.S. Patent No. 9,849,629 to Zaggl et al. It should be noted that alternatively, the polymer-reinforced membrane can be "densified" non-mechanically using heat shrinking or solvent shrinking or other suitable methods.

[0094] The "buckles" or out-of-plane structures in the membrane can have a height at least twice the thickness of the undensified membrane. Additionally, the height of the out-of-plane (i.e., Z-direction) structures can range from about 2 μm to about 2000 μm, or from about 20 μm to about 1000 μm. Additionally, the structure density in at least one direction is at least 1 buckle per mm, at least 2 buckles per mm, at least 3 buckles per mm, at least 4 buckles per mm, at least 5 buckles per mm, at least 6 buckles per mm, at least 7 buckles per mm, at least 8 buckles per mm, at least 9 buckles per mm, or at least 10 buckles per mm. In some embodiments, the structure density is 1 to 10 buckles per mm, 1 to 7 buckles per mm, 1 to 5 buckles per mm, or 1 to 3 buckles per mm.

[0095] In an alternative embodiment taught in WO 2016 / 135188 by Zaggl et al., a porous membrane having a node and fibril structure can be compressed such that little or no substantial structure is introduced in the "z" direction (i.e., fibril densification within the node and fibril structure).

[0096] Ferroelectric Materials The polymeric reinforcement membranes can be used to form composite films that support a variety of ferroelectric materials, such as ferroelectric polymers, ferroelectric ceramics, and combinations thereof. In one embodiment, the ferroelectric polymer can include ferroelectric copolymers, such as poly(vinylidene fluoride-trifluoroethylene) (VDF-TrFE), and ferroelectric terpolymers, such as poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (VDF-TrFE-CFE), poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) (P(VDF-TrFE-CTFE)), and combinations thereof. In one embodiment, the ferroelectric polymer can include poly(vinylidene fluoride-co-trifluoroethylene) (e.g., SOLVENE® 250 / P300, Solvay SA Corp., Brussels, Belgium, about 75 mol % VDF and 25 mol % TFE), poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) terpolymer p(VDF-TrFE-CTFE) (e.g., SOLVENE® T; about 63 mol % VDF, 28 mol % TrFE and 9 mol % CTFE) and combinations thereof.

[0097] Non-limiting examples include quenched thermal evaporation, vapor deposition, spray coating, slot die coating, knife over roll coating, Mayer bar coating, gravure printing, screen printing, and roller coating. The ferroelectric material can have a thickness of about 1 nm to about 20 μm, about 1 nm to about 15 μm, about 1 nm to about 10 μm, or about 1 nm to about 5 μm.

[0098] The ferroelectric material is partially or completely distributed on either surface of the polymer-reinforced membrane. In one aspect, the ferroelectric material is partially or completely distributed on either surface of the densified / structured polymer-reinforced membrane. Furthermore, the ferroelectric material can be applied to form a pattern (e.g., circles, squares, lines, or grids) on the surface of the polymer-reinforced membrane. In some embodiments, the ferroelectric material forms a monolithic (e.g., continuous) coating on the surface. In another embodiment, the ferroelectric material at least partially penetrates the thickness of the polymer-reinforced membrane. The depth of penetration can be substantially the same throughout the polymer-reinforced membrane. However, in some embodiments, the depth of partial penetration varies in the porous polymer-reinforced membrane. The porosity of the polymer-reinforced membrane facilitates the penetration of the ferroelectric material into the membrane. In a preferred embodiment, the ferroelectric material is a poly(vinylidene fluoride-co-trifluoroethylene) copolymer, a poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) terpolymer, or a combination thereof, and the polymeric reinforcement membrane is an expanded PTFE membrane having a microstructure formed primarily of fibrils or nodes interconnected by fibrils.

[0099] The polymer reinforcement film can be used to support granular ferroelectric materials such as ferroelectric ceramics, such as barium strontium titanate (BST), barium zirconium titanate (BZT), PZT (lead, zirconium, titanium, oxygen), PbTiO3 (PT), Pb(Mg 1 / 3 Nb 2 / 3 )O3(PMN), Pb(Mg 1 / 3 Nb 2 / 3)O3-PbTiO3(PMN-PT), LiTaO3 or combinations thereof. The ferroelectric ceramics can be provided in various particle shape factors such as nanoparticles, nanowires, nanorods, nanocubes, nanofillers or combinations thereof. The ferroelectric particles can be added as fillers in forming the fibrillated polymer reinforced membrane, can be applied as a coating, or combinations thereof. The ferroelectric material can be applied to the polymer reinforced membrane by known deposition and coating methods.

[0100] The polymer reinforced membrane can be used to form a composite material comprising one or more ferroelectric polymers and one or more ferroelectric ceramic particles. In one embodiment, the ferroelectric polymer and ferroelectric ceramic can be combined with the polymer reinforced membrane separately or can be combined and applied simultaneously to a polymer support membrane. In another embodiment, the ferroelectric ceramic particles are present as a filler in a fibrillated (preferably expanded PTFE) polymer reinforced membrane, after which the ferroelectric polymer and / or the ferroelectric polymer / ferroelectric ceramic particle mixture is applied (coated / imbibed).

[0101] Electrodes for ferroelectric articles Electroactive devices (i.e., sensors, actuators, etc.) are typically stimulated by applying an electric field. The ferroelectric article of the present invention comprises a composite film of ferroelectric material on a polymeric support and at least two electrodes for providing the electric field. Electrically, the ferroelectric article of the present invention typically has a thickness "d" in the range of 2-25 μm and a relative dielectric constant εr in the range of 10-55 F m. -1 The film itself is believed to be a thin, highly polar VDF-based copolymer and / or terpolymer composite film reinforced by a thin non-polar membrane (e.g., ePTFE). Two electrodes with area "A" are applied to the composite film to provide an electric field.

[0102] The capacitance is determined by the relative dielectric constant ε r The electric field is defined by the shape factor (A / d) multiplied by the electric field. The electric field polarizes the VDF-based composite film, i.e. orients the dipoles along the VDF molecular chains. Therefore, two electrodes with area A are required to build up the required electric field. Depending on the application and design specifications, the electrodes can be patterned into various shapes (rectangular, circular or comb-shaped structures). In general, the electrodes include thin films of conductive metals (Ag, Au, Al, etc.), conductive polymers (such as poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PDOT:PSS)), conductive metal oxides (such as indium tin oxide (ITO)), conductive silver nanoparticles / wires or any combination thereof.

[0103] There are a variety of techniques available for applying the conductive material to the target substrate, including but not limited to: Resistive heating of metals (Al, Ag, Au, etc.) in a vacuum chamber on a cooled substrate, Magnetron sputtering of a metal (e.g. Au) in a vacuum chamber on a cooled substrate (e.g. magnetron sputtering of Au for 30 seconds using current = 60 mA, 2 layers), Screen printing of conductive polymer and / or conductive silver nanoparticle inks, Digital printing of conductive silver nanoparticle inks; and ·Spraying conductive silver nanoparticle / wire ink through a shadow mask.

[0104] As exemplified herein, thin aluminum electrodes are -3Metal was deposited on the composite film by resistive heating in a vacuum chamber with a typical pressure of less than 10000000 mbar. The composite film was aligned and fixed on a polyethylene terephthalate / biaxially oriented polypropylene (PET / BOPP) liner, typically 25 μm to 50 μm thick. The composite film was then exposed to metal vapor. During metal deposition, the composite film was typically cooled to -30 °C. This method, known as quench deposition, ensures that the temperature profile across the composite film is much lower than the melting point of the composite film. Deposition is done by a roll-to-roll process, allowing specific lengths of homogeneous metal to be coated with minimal thickness variation. For rectangular patterning, no shadow mask is required. The width of the deposition is controlled by two mechanical shutter frames placed in close proximity to the substrate. If a pattern is required (e.g., circular electrodes), a shadow mask (made of a material such as PET) of the required pattern design is prepared by laser cutting. This patterned shadow mask is then placed on the surface of the composite film.

[0105] The thickness of the metal deposition is controlled by resistive heating power, deposition time, and monitored online by a quartz microbalance and / or optical density monitor. After the first deposition, the chamber is pressurized with nitrogen gas and the EAP composite film is carefully flipped onto the face opposite the back electrode. The shadow mask is also transferred and carefully aligned.

[0106] As exemplified herein, circular aluminum patterned electrodes were deposited on both sides of the thin composite film. The circular patterned electrodes were up to 25.4 mm to 1 / 4 inch in diameter. The thickness of the deposited aluminum film was 85 μm ± 5 μm, with a surface conductivity of 3-4 Ω.

[0107] If an overall single capacitance value is measured and the overall thickness of the film is known, the numerical value of the dielectric constant can be calculated as follows:

number

[0108] Annealing and mechanical property balance To maximize the piezoelectric response, it is desirable to maximize the crystallinity of the VDF copolymer film. This can be achieved by various annealing methods, including melting the VDF copolymer and recrystallizing it by slow cooling to promote crystal nucleation and growth. However, increased crystallinity can make monolithic VDF copolymer films brittle and reduce ductility and toughness. As demonstrated herein, reinforcing the VDF copolymer with the present polymer membrane (such as ePTFE) can significantly improve the mechanical toughness after such an annealing process.

[0109] The relative crystallinity of the films can be determined by DSC measurements. The enthalpy of the solid-state transition between ordered and disordered structures of the crystalline phase is directly related to the degree of crystallinity. As shown in Figure 2, annealing the monolithic film increased the DSC enthalpy compared to the unannealed monolithic film (Example 1 vs. Example 2, Table 1). The enthalpy of the sample held at 155°C and cooled slowly is about 2.4 times greater compared to the unannealed film. This indicates that the degree of crystallinity is about 2.4 times greater. However, as shown in Figures 3 and 4, the ductility and mechanical toughness of the annealed monolithic film is significantly reduced due to the increase in crystallinity.

[0110] The reinforcement of the VDF-TrFE copolymer in the membrane of the present invention can improve the toughness after annealing process. With reference to Table 1, the effect of annealing on this reinforced composite increases the DSC enthalpy of the VDF copolymer (about 2.5 times) (compare Example 3 and Example 4) and improves the mechanical performance when ePTFE membrane 1 (ePTFE membrane with higher strength in the machine direction than in the transverse direction) is used. The DSC enthalpy and mechanical performance of the reinforced composite using ePTFE membrane with a more balanced strength profile (i.e., ePTFE membrane 2) are shown in Table 1, comparing Examples 5 and 6. The crystallinity increases (about 2.8 times) with annealing, and balanced mechanical performance is observed in both the machine direction and the transverse direction.

[0111] Test Method Scanning Electron Microscopy (SEM) - Cross-Sectional Sample Preparation and Imaging SEM images were collected using a field emission scanning electron microscope (ZEISS Gemini SEM 500, Zeiss International, Oberkochen, Germany). Cross-sectional samples were prepared using the cooled razor blade method and mounted on 12.5 mm diameter metal stubs using carbon double-sided adhesive pads (SpectroTabs, Plano GmbH, Wetzlar, Germany). The mounted samples were sputter-coated with platinum.

[0112] Thickness measurement The thickness of the films was determined from cross-sectional SEM images.

[0113] Mass per area / composition measurement The mass per area was determined by measuring the mass of a 80 mm diameter circle cut from the film. The composition, i.e. the mass fraction of the electroactive VDF copolymer or terpolymer in the film, was determined from the ratio of the VDF copolymer or terpolymer laydown in the coating process and the measured mass per area of ​​the film.

[0114] Mechanical Tensile Test Static and dynamic mechanical tensile tests were performed on a Z050 universal testing machine (ZwickRoell GmbH & Co. KG, Ulm, Germany) equipped with a 200 N load cell and, unless otherwise stated, were controlled by the instrument manufacturer's software (testXpert III) using default parameters set by the manufacturer (ZwickRoell, supra).

[0115] Briefly, rectangular samples with dimensions of (25.4x5)mm were prepared with a cutting tool and placed between the clamping mechanism with a sample loading tool from the outside. A preforce of 0.01N and a constant linear pulling speed of 200mm / min were used for static tensile measurements. The tests were performed at room temperature (approximately 21°C).

[0116] Dynamic tests were performed on the same testing machine and similar sample dimensions. A cyclic procedure with 10 repeated cycles of cyclic trapezoidal force loading was applied to the specimens. The setup was performed by the flexible programming language ZIMT (ZwickRoell Interpreter for Materials Testing, ZwickRoell, mentioned above). A total 1.5% elongation range within the elastic region was selected to acquire the cyclic force data.

[0117] Differential scanning calorimetry (DSC) measurement DSC data were collected using a TA Instruments Q2000 DSC (TA Instruments, New Castle, DE) between -50 °C and 155 °C at a heating rate of 10 °C / min. Samples with masses of approximately 7–8 mg were loaded into the sample holder for testing. Enthalpies of solid-state transitions were determined using the integration function included in the software.

[0118] DC Voltage Breakdown Method The test procedure was based on ASTM D3755-97 (2004). In this method, more than 25 individual test points are directly contacted between electrodes made of metalized biaxially oriented polypropylene. A 3 mil thick Kapton film with a 0.25 inch diameter circular hole (or window) defined in it is placed on top of the test film to limit the location and size of the contact area. Contact to the film occurs only within the hole in the Kapton film, between the lower and upper metalized polypropylene films. An Associated Research Hypot Dielectric Analyzer Model 7720 is used to increase the voltage at 500 V / s until breakdown occurs, at which point the voltage is recorded. A continuous probability distribution (Wabull distribution function) is applied for data evaluation.

[0119] Electric Polarization Method Standard AC polarization techniques were used as described in the literature (Qiu et al., J. Appl. Phys. (2013), 113: 224106-1~224106-8). A modified Sawyer-Tower circuit (Qui et al., supra) and a combination of unipolar and bipolar voltage waveforms were used to record the polarization vs electric field hysteresis curves of VDF-based copolymer / terpolymer composite films. Hysteresis is an essential feature of ferroelectric materials and can also be used to determine some of their key properties.

[0120] d 33 Measuring Station Piezoelectric coefficient d 33was measured according to the Berlincourt method (Stewart M., Cain MG (2014) Direct Piezoelectric Measurement: The Berlincourt Method. In: Characterisation of Ferroelectric Bulk Materials and Thin Films. Springer Series in Measurement Science and Technology, Vol. 2, Cain, M(editor), Springer, Dordrecht). The piezoelectric coefficient d 33 To determine the piezoelectric coefficient, the sample is placed under an electrodynamic shaker and subjected to a static force of 3 N. The shaker vibrates at 2 Hz and exerts a sinusoidal force with an amplitude of 1 N. The charge generated by the piezoelectric effect in the sample is amplified by a charge amplifier and displayed on an oscilloscope. The dynamic force is measured by a force sensor and displayed on an oscilloscope. Both curves were used to determine the piezoelectric coefficient from the quotient of the charge signal and the dynamic force. The piezoelectric coefficient d 33 We also developed a commercially available piezometer system (d 33 The measured values ​​were determined using a PiezoMeter System Model PM300 (Piezotest Pte. Ltd., Singapore). Briefly, the test sample is clamped in the system and subjected to a low frequency force. By processing the electrical signal from the sample and comparing it with a built-in reference, the system determines the d 33 can be read directly.

[0121] Expanded polytetrafluoroethylene (ePTFE) membrane In this example, the following ePTFE membranes were used:

[0122] "ePTFE membrane 1" - Preparation of ePTFE membrane The ePTFE membrane was manufactured following the general teachings set forth in U.S. Patent No. 5,476,589 to Bacino. The ePTFE membrane was similar to "ePTFE Membrane 3" (below), but had an areal density (mass / area) of approximately 3 g / m 2 It's expensive.

[0123] "ePTFE membrane 2" - Preparation of ePTFE membrane The ePTFE membrane was manufactured according to the general teachings set forth in U.S. Patent No. 7,306,729 to Bacino et al. The ePTFE membrane had a mass per area of ​​approximately 3.8 g / m 2 , a non-contact thickness of about 14.2 μm, a bubble point of about 481 kPa, a machine direction matrix tensile strength of about 343 MPa, and a transverse direction matrix tensile strength of about 268 MPa.

[0124] "ePTFE membrane 3" - Preparation of ePTFE membrane The ePTFE membrane was manufactured according to the general teachings set forth in U.S. Patent No. 5,476,589 to Bacino. The ePTFE membrane had a mass per area of ​​approximately 2.1 g / m. 2 , non-contact thickness of about 7.4 μm, bubble point of about 271 kPa, machine direction matrix tensile strength of 1058 MPa, and transverse direction matrix tensile strength of about 93.6 MPa.

[0125] "ePTFE membrane 4" - Preparation of structured ePTFE membrane The ePTFE membrane was manufactured according to the general teachings set forth in U.S. Patent No. 7,306,729 to Bacino et al. The ePTFE membrane had a mass per area of ​​approximately 0.2 g / m 2 , non-contact thickness of about 1 μm, bubble point of about 407 kPa, machine direction matrix tensile strength of 734 MPa, and transverse direction matrix tensile strength of about 755 MPa.

[0126] The ePTFE membrane was uniaxially structured in the transverse direction at a ratio of 1:1.5 according to the teachings set forth in U.S. Patent No. 9,849,629 to Zaggl et al. After structuring, the densified membrane was subjected to an imbibition process.

[0127] Piezoelectric and Ferroelectric Polymers In this example, the following polymer resins were used: Poly(vinylidene fluoride-co-trifluoroethylene) A poly(vinylidene fluoride-co-trifluoroethylene) copolymer was used, which has piezoelectric, pyroelectric and ferroelectric properties (SOLVENE® 250 / P300, Solvay SA Corp. Brussels, Belgium, CAS number 28960-88-5). The resin contains about 75 mol % VDF and 25 mol % TrFE. SOLVENE® 250 / P300 P(VDF-TrFE) copolymer has the following properties: Melting point: 146°C Average molecular weight: 300kDa Elastic modulus 1000MPa Curie temperature: 116℃ Crystallization temperature: 120℃ Density (film): 1.7g / cm 3 ε r (25℃; 1kHz):11F·m -1 Breakdown voltage: >280V / μm Piezoelectric coefficient (d33): -24pC / N at 110Hz

[0128] Poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) terpolymer Poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) terpolymer p(VDF-TrFE-CTFE) (SOLVENE® T EAP (Solvay SA Corp., Brussels, Belgium) was used. This terpolymer is about 63 mol % VDF, 28 mol % TrFE and 9 mol % CTFE. The p(VDF-TrFE-CTFE) terpolymer is a high dielectric constant iron relaxor polymer. The p(VDF-TrFE-CTFE) terpolymer has the following properties: Melting point: 115℃ Average molecular weight: 300kDa Elastic modulus: 200MPa Crystallization temperature: 85℃ Curie temperature: 16℃ Density (film): 1.7g / cm 3 Breakdown voltage: >300V / μm ε r (25℃; 1kHz) 45F·m -1

[0129] Application of electrodes to composite films A thin aluminum electrode (circular, 15 mm in diameter) was placed on the -3 Deposition was performed by resistive heating in a vacuum chamber with typical pressures below mbar. The composite film is typically aligned and fixed on a PET / BOPP liner with a thickness of 25 μm to 50 μm. It is then exposed to metal vapor. During metal deposition, the film is typically cooled to -30 °C. This method, known as quench deposition, allows the temperature profile across the composite film to be much lower than the melting point of the composite film. Deposition is performed in a roll-to-roll process, allowing specific lengths of homogeneous metal to be coated with minimal thickness variation. No shadow mask is required for rectangular patterning. The width of the deposition is controlled by two mechanical shutter frames placed in close proximity to the substrate. If a pattern is required (e.g. circular electrodes), a shadow mask (e.g. PET) of the required pattern design is prepared by laser cutting. This patterned shadow mask is then placed on the surface of the composite film.

[0130] The thickness of the metal deposition is controlled by resistive heating power and deposition time, and monitored online by a quartz microbalance and / or optical density monitor. After the first deposition, the chamber is pressurized with nitrogen gas, the composite film is carefully flipped to the other side, and a second electrode is applied. A shadow mask is transferred and carefully zoned so that the two electrodes are aligned. The thickness of the deposition is typically in the range of 60-85 nm.

[0131] For hysteresis measurements, electrodes were attached to both sides of the sample. In corona polarized samples, the electrodes were applied first after polarization. The method was the same as for the electrodes for hysteresis measurements. EXAMPLES

[0132] example Example 1 A solution of 10% by weight poly(vinylidene fluoride-co-trifluoroethylene) copolymer resin (SOLVENE® 250 / P300, Solvay SA Corp, supra) and methyl ethyl ketone (MEK) was prepared by mixing the components and stirring for 4 hours at room temperature (nominal 24° C.). The resulting solution was applied directly to a carrier film using a slot die in a continuous roll-to-roll process. The film was dried in an in-line oven to remove the solvent. A cross-sectional SEM image of the monolithic cast film was collected and shown in FIG. 1. The film was approximately 3.6 μm thick as measured by SEM. Differential scanning calorimetry (DSC) analysis was performed. A DSC plot of the monolithic cast film is shown as FIG. 2 (top). The enthalpy of the solid state crystalline transition obtained by integration is 8.7167 Joules / gram. Tensile tests (elongation vs. force) were performed on the monolithic cast film as described in the Test Methods section. Tensile test results in the machine (downweb) direction (MD) of the monolithic cast film are shown in Figure 3 (Example 1, solid line). Tensile test results in the cross (crossweb) direction (TD) of the monolithic cast film are shown in Figure 4 (Example 1, solid line). Characterization results for Example 1 are summarized in Table 1.

[0133] Example 2 The monolithic film of Example 1 was annealed in an oven set at 155° C. for 10 minutes. The oven was then turned off and the film was left in the oven until it reached room temperature (nominal 24° C.) and the film was allowed to cool slowly. A cross-sectional SEM image of the annealed film is shown in FIG. 5, where the thickness of the annealed film is about 4.8 μm. DSC was performed and the resulting plot is shown in FIG. 2 (Example 2, dashed line). The enthalpy of the solid-state crystalline transition obtained by integration is about 22.051 J / g. The ratio of the enthalpy of the annealed film to that of the unannealed monolithic film of Example 1 indicates that the annealing treatment increased the crystallinity of the film by a factor of 2.5. Tensile testing was performed as described in Example 1, and the elongation vs. force plots are shown in FIG. 3 (machine direction, dashed line) and FIG. 4 (transverse direction, dashed line). Voltage breakdown testing was performed as described in the Test Methods section above. The voltage breakdown results are shown graphically in the Weibull plot of Figure 6, and the Weibull parameters α and β were determined. Electric polarization measurements were performed as described in the Test Methods section. A plot of the polarization results (field vs. polarization) is shown in Figure 7. Characterization data is summarized in Table 1.

[0134] Example 3 A 10 wt% solution of Example 1 (poly(vinylidene fluoride-co-trifluoroethylene) copolymer resin dissolved in MEK) was applied to a microporous ePTFE membrane ("ePTFE Membrane 1") using a slot die in a continuous roll-to-roll process. The solution uniformly wetted and filled the ePTFE membrane. The film was dried in an in-line oven to remove the solvent. The resulting composite film had a composition of 39 wt% poly(vinylidene fluoride-co-trifluoroethylene) copolymer resin and 61 wt% ePTFE. A cross-sectional SEM image of the composite film is shown in Figure 8. DSC analysis was performed to measure enthalpy (normalized). Tensile tests were performed to measure elongation vs. force (MD and TD). Voltage breakdown tests were performed to determine the Weibull parameters α and β. Characterization results are summarized in Table 1.

[0135] Example 4 The composite film of Example 3 was annealed by placing it in an oven set at a temperature of 155°C for 10 minutes. The oven was then turned off and the film was left in the oven until it reached room temperature (nominal 24°C) and was allowed to cool slowly. A cross-sectional SEM image of the annealed composite film is shown in Figure 9. DSC analysis was performed to measure enthalpy (normalized). Tensile tests were performed to measure elongation vs. force (MD and TD). Voltage breakdown tests were performed to measure the Wavell parameters α and β. Electrical polarization measurements were performed and the polarization results are shown in Figure 10. The property data are summarized in Table 1.

[0136] Example 5 A 10 wt% solution of Example 1 (poly(vinylidene fluoride-co-trifluoroethylene) copolymer resin dissolved in MEK) was applied directly to a microporous ePTFE membrane ("ePTFE Membrane 2") using a slide die in a continuous roll-to-roll process. The solution uniformly wetted and filled the ePTFE membrane. The film was dried in an in-line oven to remove the solvent. The composite film had a composition of 43 wt% poly(vinylidene fluoride-co-trifluoroethylene) copolymer resin and 57 wt% ePTFE. A cross-sectional SEM image of the composite film is shown in FIG. 11.

[0137] DSC analysis was performed to measure enthalpy (normalized). Tensile tests were performed to measure elongation vs. force (MD and TD). Voltage breakdown tests were performed to determine the Weibull parameters α and β. The property data are summarized in Table 1.

[0138] Example 6 The composite film of Example 5 was annealed by placing it in an oven set at a temperature of 155° C. for 10 minutes. The oven was then turned off and the film was left in the oven until it reached room temperature (nominal 24° C.) and was allowed to cool slowly.

[0139] DSC analysis was performed to measure enthalpy (normalized). Tensile tests were performed to measure elongation vs. force (MD and TD). Voltage breakdown tests were performed to determine the Weibull parameters α and β. Electrical polarization measurements were performed and the polarization results are shown in FIG. 12. The property data are summarized in Table 1.

[0140] Example 7 The following examples describe the preparation of multilayer VDF-based copolymer films.

[0141] Monolithic films of poly(vinylidene fluoride-co-trifluoroethylene) copolymer resins were produced using the general process of Example 1. ePTFE composite films containing poly(vinylidene fluoride-co-trifluoroethylene) copolymer resins were produced according to Example 5. Multilayering of several VDF-based copolymer films was achieved by a two-step approach under temperature and high pressure for a specific residence time. For this purpose, a commercially available high-performance heated press (model P200 S from COLLIN Lab & Pilot Solutions GmbH) was used. The hot plate was heated to 155° C. and the films were bonded at a pressure of 50 bar in both process steps.

[0142] First, the monolithic films with ePTFE composite films were stacked and manually aligned. A high temperature silicone rubber sheet (HT60, Silex Silicone LTD, Hampshire, UK) was used as a liner to separate the stacked films from the hot plate to prevent surface irregularities between the polymer stack and the hot plate. The aligned stack was then compressed between the hot plates at 155 °C and 50 bar for 30 min. The heated press was opened and the two-layer bonded stack was allowed to cool slowly.

[0143] One of the silicone liners was then manually removed from one side of the two-layer stack and a third layer (a monolithic film of poly(vinylidene fluoride-co-trifluoroethylene) copolymer resin, Example 1) was placed onto the VDF-based surface of the two-layer stack. Once again, the silicone liner was used to separate the stack sheet from the hotplate surface. The three-layer stack was compressed together using the same process parameters (155° C., 50 bar for 30 minutes).

[0144] The resulting multilayer composite film had a composition of 71 wt% poly(vinylidene fluoride-co-trifluoroethylene) copolymer resin (Solvene® 250 / P300) and 19 wt% ePTFE. A cross-sectional SEM image of the three-layer film is shown in FIG. 13. The results of the polarization experiment are shown in FIG. 14. The property data are summarized in Table 1.

[0145] Example 8 A solution of 10 wt. % poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) terpolymer p(VDF-TrFE-CTFE) (Solvene® T resin, Solvay SA Corp., supra) and methyl ethyl ketone was prepared by mixing the components and stirring for 4 hours at room temperature (nominal 24° C.). The solution was applied to a microporous ePTFE membrane ("ePTFE membrane 2") using a slot die in a continuous roll-to-roll process. The solution uniformly wetted and filled the ePTFE membrane. The film was dried in an in-line oven to remove the solvent. The resulting composite film had a composition of 53 wt. % p(VDF-TrFE-CTFE) (Solvene® T) and 47 wt. % ePTFE. The composite film was annealed in an oven set at 125° C. for 10 minutes. The oven was then turned off and the film was left in the oven to slowly cool to room temperature (nominal 24° C.) over a period of approximately 24 hours.

[0146] Cross-sectional SEM image analysis was used to measure the thickness of the composite films. DSC analysis was performed to measure the enthalpy (normalized). Voltage breakdown tests were performed to determine the Wavell parameters α and β. Electrical polarization measurements were performed and the polarization results are shown in Figure 15. The property data are summarized in Table 1.

[0147] Example 9 A 10 wt % solution of poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) terpolymer p(VDF-TrFE-CTFE) (SOLVENE® T resin, Solvay SA Corp, supra) was prepared and applied to the ePTFE as described in Example 8, except the ePTFE membrane used was "ePTFE Membrane 3." The solution uniformly wetted and filled the ePTFE membrane. The film was dried in an in-line oven to remove the solvent. The resulting composite film had a composition of 52 wt % p(VDF-TrFE-CTFE) (Solvene® T) and 48 wt % ePTFE. The composite film was placed in an oven set at a temperature of 125° C. and annealed for 10 minutes. The oven was then turned off and the film was left in the oven to slowly cool to room temperature (nominal 24° C.) over a period of approximately 24 hours.

[0148] Cross-sectional SEM image analysis was used to determine the thickness of the composite films. DSC analysis was performed to measure the enthalpy (normalized). Voltage breakdown tests were performed to determine the Wavelet parameters α and β. Electric polarization measurements were performed and the polarization results are shown in Figure 16. The property data are summarized in Table 2.

[0149] Example 10 Example 10 was processed in two steps. A microporous PTFE membrane ("ePTFE membrane 4") was uniaxially structured in the transverse direction in a ratio of (1.0:1.5) as described in U.S. Patent No. 9,849,629 to Zaggl et al. A solution of 10 wt% p(VDF-TrFE-CTFE) (Solvene® T resin, Solvay, supra) and methyl ethyl ketone was prepared by mixing the components and stirring for 4 hours at room temperature (nominal 24°C). The solution was applied to the structured microporous PTFE membrane in a continuous roll-to-roll process using a slot die. The composite film was annealed by placing it in an oven set at a temperature of 125°C for 10 minutes. The oven was then turned off and the film was left in the oven to slowly cool for approximately 24 hours until it reached room temperature (nominal 24°C). The resulting composite film had a composition of 84 wt% VDF-based terpolymer and 16 wt% ePTFE.

[0150] Cross-sectional SEM image analysis was used to determine the thickness of the composite films. Electric polarization measurements were performed and the polarization results are shown in Figure 17. The property data are summarized in Table 2.

[0151] Example 11 Example 11 was processed in two steps. A structured microporous PTFE membrane was prepared as described in Example 10. A solution of 10 wt% p(VDF-TrFE-CTFE) (SOLVENE® T resin, Solvay, supra) and methyl ethyl ketone was prepared by mixing the components and stirring for 4 hours at room temperature (nominal 24° C.). The p(VDF-TrFE-CTFE) solution was applied to the structured microporous PTFE membrane using a slot die in a continuous roll-to-roll process. The composite film was annealed and cooled as described in Example 10. The resulting composite film had a composition of 98 wt% VDF-based terpolymer and 2 wt% ePTFE.

[0152] Cross-sectional SEM image analysis was used to determine the thickness of the composite films. Electric polarization measurements were performed and the polarization results are shown in Figure 18. The property data are summarized in Table 2.

[0153] Example 12 A composite ePTFE film containing p(VDF-TrFE-CTFE) was prepared and dried according to the method of Example 8, but with a high loading of VDF terpolymer. The resulting composite film had a composition of 60 wt% VDF terpolymer and 40 wt% ePTFE. The composite film was annealed by placing it in an oven set at a temperature of 125°C for 30 minutes. The oven was then turned off and the film was left in the oven to slowly cool to room temperature (nominal 24°C) over a period of approximately 24 hours. A SEM image of the cross section of the film is shown in Figure 19. The results of the mechanical tensile tests in the machine direction (MD) and transverse direction (TD) are shown in Figure 20 (solid line, Example 12). The results of the polarization experiment are shown in Figure 21. The property data are summarized in Table 2.

[0154] Example 13 Composite ePTFE films containing p(VDF-TrFE-CTFE) were prepared and dried similarly to the method of Example 8, but with different loadings of VDF terpolymer. The resulting composite films had a composition of 47 wt% VDF terpolymer and 53 wt% ePTFE. The composite films were annealed and cooled as described in Example 12.

[0155] Cross-sectional SEM image analysis was used to measure the thickness of the composite films. Electric polarization measurements were performed and the polarization results are shown in Figure 22. The property data are summarized in Table 2.

[0156] Example 14 A structured microporous PTFE membrane was prepared and dried using the methods described in Examples 10 and 11, but using a higher loading of VDF terpolymer. The resulting structured composite film had a composition of 85 wt% VDF terpolymer and 15 wt% ePTFE. The structured composite film was annealed and cooled as described in Example 13.

[0157] Cross-sectional SEM image analysis was used to measure the thickness of the composite films. The results of the mechanical tensile tests in the machine direction (MD) and transverse direction (TD) are shown in Figure 20 (dashed line, Example 14) and Figure 23. The results of the polarization experiments are shown in Figure 24. The property data are summarized in Table 2.

[0158] Example 15 Stacked multilayer films were fabricated to make a 5-layer composite using the general heat pressing process described in Example 7 with modified process parameters described below. Briefly, 5 layers of the composite film of Example 13 (composite ePTFE film with p(VDF-TrFE-CTFE)) were aligned and stacked in a press. A silicone liner was used to separate the top and bottom of the 5-layer stack from the hotplate surface. A pressure of 0.17 bar (2.5 psi) was applied for 10 minutes at a temperature of 110°C. The press was opened and allowed to cool to room temperature (nominal 14°C). The 5-layer composite film was annealed and cooled as described in Example 12. The resulting 5-layer composite film had a composition of 47 wt% VDF terpolymer and 53 wt% ePTFE. An SEM image of the cross section of the film is shown in Figure 25. The results of the polarization experiment are shown in Figure 26. The property data are summarized in Table 2.

[0159] Example 16 The structured ePTFE composite film of Example 14 was used to make a five-layer composite film as described in Example 15. Briefly, the five layers of the structured composite film of Example 14 were aligned and stacked in a press. Silicone liners were used to separate the top and bottom of the five-layer stack from the hotplate surface. Heat pressing and annealing were performed as described in Example 15. The resulting five-layer composite film had a composition of 84 wt% VDF terpolymer and 6 wt% ePTFE.

[0160] Cross-sectional SEM image analysis was used to measure the thickness of the five-layer composite films. The results of the poling experiments are shown in Figure 27. The property data are summarized in Table 2.

[0161] Example 17 A monolithic film of poly(vinylidene fluoride-co-trifluoroethylene) copolymer resin (SOLVENE® 250 / P300, Solvay SA Corp, supra) was prepared and annealed according to the general process of Example 2.

[0162] Cross-sectional SEM image analysis was used to determine the thickness of the monolithic films. The property data are summarized in Table 2.

[0163] Example 18 The following example describes the preparation and performance of a laminated three-layer composite film having one ePTFE / VDF terpolymer composite film sandwiched between two VDF copolymer monolithic films.

[0164] Briefly, the VDF-based terpolymer composite film of Example 14 was symmetrically placed between two monolithic VDF copolymer films of Example 17 to form a multi-layer composite film by the general hot pressing process described in Example 7. The bonding process itself was similar to that described in Example 7 and was carried out in two steps using a hot press.

[0165] A bilayer film was first prepared by stacking and bonding the ePTFE / VDF-based terpolymer composite film of Example 14 with the first monolithic film of Example 17 at 125°C and 50 bar. Silicone liners were used to separate the top and bottom of the bilayer stack from the hotplate surface. After this first lamination step, the resulting bilayer composite film was slowly cooled to room temperature (nominal 24°C). The support liner was carefully removed from the bilayer stack. The second monolithic film of Example 17 was manually aligned and bonded (using the same temperature and pressure) to the other side of the bilayer composite film to form a symmetrical three-layer composite.

[0166] The resulting multilayer composite film, consisting of these three monolayers, had the composition 67 wt% p(VDF-TrFE) (SOLVENE® 250 / P300), 28 wt% p(VDF-TrFE-CTFE) (SOLVENE® T) and 5 wt% ePTFE. A cross-sectional SEM image of the three-layer film is shown in FIG. 28. The approximate total thickness (16.46 μm) was determined by adding the thicknesses of the individual layers measured by SEM. The results of the polarization experiment are shown in FIG. 29. The characterization data are summarized in Table 2.

Table 1

Table 2

Claims

1. a. a composite film having a first surface and a second surface, i. a ferroelectric material, and ii. a polymer-reinforced membrane; A composite film comprising: b. a first electrode electrically connected to a first surface of the composite film; and c. a second electrode electrically connected to a second surface of the composite film; 1. A ferroelectric article comprising:

2. The ferroelectric article of claim 1 , wherein the polymer reinforced film comprises a densified and / or contracted film comprising macrostructural folds and / or microfolded fibrils.

3. The ferroelectric article of claim 1 , wherein the ferroelectric material comprises a ferroelectric polymer, a ferroelectric ceramic, or a combination thereof.

4. The ferroelectric article of any one of claims 1 to 3, wherein the ferroelectric polymer comprises a vinylidene difluoride (VDF) copolymer or terpolymer.

5. The ferroelectric article of any one of claims 1 to 4, wherein the ferroelectric polymer comprises one or more of poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (VDF-TrFE-CFE), poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) (P(VDF-TrFE-CTFE), poly(vinylidene fluoride-trifluoroethylene) (VDF-TrFE), or combinations thereof.

6. The ferroelectric ceramics include barium strontium titanate (BST), barium zirconium titanate (BZT), PZT (lead, zirconium, titanium, oxygen), and PbTiO 3 (PT), Pb(Mg 1 / 3 Nb 2/3 ) O 3 (PMN), Pb(Mg 1/3 Nb 2 / 3 ) O 3 -PbTiO 3 (PMN-PT), LiTaO 3 The ferroelectric article of any one of claims 1 to 5, comprising one or more of:

7. The ferroelectric article of any one of claims 1 to 6, wherein the ferroelectric ceramic comprises one or more of nanoparticles, nanowires, nanorods, nanocubes, nanofillers, or combinations thereof.

8. The ferroelectric article of any one of claims 1 to 7, wherein the ferroelectric material comprises a ferroelectric polymer and a ferroelectric ceramic particle filler.

9. The ferroelectric article of any one of claims 1 to 8, wherein the polymeric reinforcement membrane comprises a microporous membrane having pores, the microporous membrane comprising a polyolefin, a fluorinated polyolefin, or a combination thereof.

10. 10. The ferroelectric article of any one of claims 1 to 9, wherein the polymer reinforcement membrane comprises one or more of ultra-high molecular weight polyethylene (UHMWPE), polytetrafluoroethylene (PTFE), polyparaxylylene (PPX), vinylidene fluoride (VDF) copolymer (VDF-co-TFE or TrFE), ethylene tetrafluoroethylene (ETFE), poly(tetramethyl-p-silphenylene siloxane) (PTMPS), or combinations thereof.

11. The ferroelectric article of any one of claims 1 to 10, wherein the polymer reinforced membrane comprises an expanded polymer having a microstructure of nodes interconnected by fibrils and a void volume defining a plurality of pores, an expanded polymer having a substantially only fibril microstructure and a void volume defining a plurality of pores, or a combination thereof.

12. 12. The ferroelectric article of claim 11, wherein the expanded polymer comprises one or more of expanded polytetrafluoroethylene (ePTFE), expanded ultra-high molecular weight polyethylene (ePE), expanded polyparaxylylene (ePPX), expanded VDF-co-TFE copolymer, expanded VDF-co-TrFE copolymer, expanded ethylene tetrafluoroethylene (eETFE), expanded poly(tetramethyl-p-silphenylene siloxane (ePTMPS), or combinations thereof.

13. 13. The ferroelectric article of claim 11 or 12, wherein the expanded polymer node, fibril or combination thereof microstructure is partially or completely coated with a conductive metal coating to define a coated microstructure, and further wherein the coated microstructure retains at least a portion of the void volume after coating.

14. The ferroelectric article of any one of claims 1 to 13, wherein the ferroelectric material forms a coating on the reinforcing film.

15. The ferroelectric article of claim 11 or 12, wherein the ferroelectric material is partially or completely absorbed within a void volume of the reinforced membrane.

16. 16. The ferroelectric article of any one of claims 1 to 15, wherein the ferroelectric polymer comprises one or more of poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (VDF-TrFE-CFE), poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) (P(VDF-TrFE-CTFE)), poly(vinylidene fluoride-trifluoroethylene) (VDF-TrFE), or combinations thereof, and further wherein the ferroelectric polymer is partially or fully absorbed within a reinforcing membrane of expanded ePTFE.

17. The ferroelectric article of any one of claims 1 to 16, wherein the composite film has a thickness of at least 1 µm and at most 20 µm.

18. The ferroelectric article of claim 17, wherein the composite film has a thickness of at least 1 μm and at most 10 μm.

19. The polymer-reinforced membrane has a mass per area of ​​5 g / m 2 The ferroelectric article of any one of claims 1 to 18, wherein:

20. The polymer-reinforced membrane has a mass per area of ​​4 g / m 2 20. The ferroelectric article of claim 19, wherein:

21. The polymer-reinforced membrane has a mass per area of ​​3 g / m 2 20. The ferroelectric article of claim 19, wherein:

22. The composite film has a total mass, and further comprises: a. a reinforcing membrane of 20 wt % or less based on the total weight of the composite film; and b. 80 wt % or more of a ferroelectric material based on the total weight of the composite film; The ferroelectric article of any one of claims 1 to 21, comprising:

23. The composite film has a total mass, and further comprises: a. a reinforcing membrane of 15 wt % or less based on the total weight of the composite film; and b. 85 wt % or more of a ferroelectric material based on the total weight of the composite film; The ferroelectric article of any one of claims 1 to 22, comprising:

24. The composite film has a total mass, and further comprises: a. a reinforcing membrane of 10 wt % or less based on the total weight of the composite film; and b. 90 wt % or more of a ferroelectric material based on the total weight of the composite film; The ferroelectric article of any one of claims 1 to 23, comprising:

25. The reinforcing membrane is biaxially oriented; c. a machine direction (MD) matrix tensile strength of at least 30 MPa; and d. a transverse direction (TD) matrix tensile strength of at least 30 MPa; The ferroelectric article of any one of claims 1 to 24.

26. 20. The ferroelectric article of claim 19, wherein the ratio of MD matrix tensile strength to TD matrix tensile strength is from 1.0:0.1 to 0.1:1.

0.

27. The ferroelectric article of any one of claims 19 to 21, wherein the reinforcing film comprises a porosity of at least 30%, measured prior to the addition of the ferroelectric material.

28. The upper electrode and / or the lower electrode are a) a layer of conductive metal of alumina up to 80 nm thick; b) a layer of conductive thermoplastic of poly(3,4-ethylenedioxythiophene) polystyrenesulfonate (PEDOT:PSS); c) a layer of conductive ink comprising silver nanoparticles or silver nanowire ink deposited by digital printing, spraying, screen printing, or d. any combination of a, b, or c; The ferroelectric article of any one of claims 1 to 27, comprising:

29. The ferroelectric article of any one of claims 1 to 28, wherein the ferroelectric composite comprises multiple composite films in a stack configuration.

30. 30. The ferroelectric article of claim 29, wherein the plurality of composite films comprises at least one laminated structure.

31. 31. The ferroelectric article of claim 28 or 30, wherein at least one of the composite films in the stack configuration is different from at least one of the other composite films in the material.

32. The ferroelectric article of any one of claims 28 to 31, wherein at least one of the composite films in the stack configuration is of a different thickness than at least one of the other films in the material.

33. The ferroelectric article of any one of claims 28 to 32, wherein at least one of the composite films in the stack configuration has a different strength than at least one of the other films in the material.

34. The ferroelectric article of any one of claims 27 to 31, wherein at least one of the composite films in the stack configuration is oriented differently than at least one of the other films within the material.

35. A device comprising the ferroelectric article of any one of claims 1 to 34.

36. 1. A method for making a ferroelectric article, comprising the steps of: providing a polymeric reinforced membrane having a first surface and a second surface, wherein said polymeric reinforced membrane has a microstructure of nodes interconnected by fibrils or has a microstructure of substantially only fibrils, said microstructure further defining a void volume defining a plurality of pores; applying a ferroelectric material to the polymer reinforced film to form a reinforced ferroelectric composite; attaching at least one first electrode to the first surface; and connecting at least one second electrode to said second surface to form a ferroelectric article; A method comprising:

Citation Information

Patent Citations

  • Piezoelectric laminate

    JP2015035576A

  • Piezoelectric element and method of manufacturing the same

    JP2016072355A

  • Forming a piezoelectric membrane

    US20140134418A1